Membangun Kompetensi Wirausaha Pengrajin Hiasan Dinding Desa Tegalalang Gianyar Bali - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti; I Made Hedy Wartana; I Ketut Yudana Adi (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2025)
The Wall Decor craft industry in Tegalalang Village, Bali, is a vital economic sector contributing to local and international markets. However, its sustainability is threatened. This community service program aimed to enhance the business capabilities of Wall Decor craftsmen through targeted training in entrepreneurial competence, and market expansion strategies. A participatory action research approach was employed, engaging twelve Wall Decor craftsmen in a structured intervention program. The initiative included pre-test and post-test assessments of entrepreneurial competence, interactive capacity-building workshops, and mentorship programs. Training sessions covered essential entrepreneurial dimensions such as goal setting, risk-taking, innovation, and resilience. A digital marketing component was also introduced to help craftsmen expand their market reach. The results demonstrated substantial improvements across all twelve dimensions of entrepreneurial competence. Notable gains were observed in resilience, need for achievement, and self-efficacy, indicating a positive shift in business confidence and strategic planning. Participants showed increased willingness to innovate and take calculated risks, essential for sustaining competitive business operations. Despite these improvements, trustworthiness and patience exhibited the least progress, highlighting the need for continued emphasis on ethical business practices and long-term financial planning. The findings underscore the transformative impact of structured entrepreneurial training in traditional craft industries. By integrating digital marketing strategies and fostering business resilience, this program contributed to enhancing market competitiveness. Future interventions should focus on sustaining these advancements through long-term mentorship, cooperative formation, and broader financial inclusion initiatives.